Tobacco Retail Outlets, Neighborhood Deprivation and the Risk of Prenatal Smoke Exposure. Issue 12 (19th July 2022) - Wheeler, David C; Boyle, Joseph; Jeremy Barsell, D; Maguire, Rachel L; Zhang, Junfeng (Jim); Oliver, Jason A; Jones, Shaun; Dahman, Bassam; Murphy, Susan K; Hoyo, Cathrine; Baggett, Chris D; McClernon, Joseph; et al.
Abstract: Introduction: Smoking and smoke exposure among pregnant women remain persistent public health issues. Recent estimates suggest that approximately one out of four nonsmokers have measurable levels of cotinine, a marker indicating regular exposure to secondhand smoke. Epidemiological research has attempted to pinpoint individual-level and neighborhood-level factors for smoking during pregnancy. However, most of these studies have relied upon self-reported measures of smoking. Aims and Methods: To more accurately assess smoke exposure resulting from both smoking and secondhand exposure in mothers during pregnancy, we used Bayesian regression models to estimate the association of cotinine levels with tobacco retail outlet (TRO) exposure and a neighborhood deprivation index (NDI) in six counties in North Carolina centered on Durham County. Results: Results showed a significant positive association between TRO exposure (β = 0.008, 95% credible interval (CI) = [0.003, 0.013]) and log cotinine after adjusting for individual covariates (eg, age, race/ethnicity, education, marital status). TRO exposure was not significant after including the NDI, which was significantly associated with log cotinine (β = 0.143, 95% CI = [0.030, 0.267]). However, in a low cotinine stratum (indicating secondhand smoke exposure), TRO exposure was significantly associated with log cotinine (β = 0.005, 95% CI = [0.001, 0.009]), while in a high cotinine stratum (indicating active smoking), the NDI was significantly associated with log cotinine (β = 0.176, 95% CI = [0.005, 0.372]). Conclusions: In summary, our findings add to the evidence that contextual factors are important for active smoking during pregnancy. Implications: In this study, we found several significant associations that suggest a more nuanced understanding of the potential influence of environmental- and individual-level factors for levels of prenatal smoke exposure. Results suggested a significant positive association between TRO exposure and cotinine levels, after adjusting for the individual factors such as race, education, and marital status. Individually, NDI was similarly positively associated with cotinine levels as well. However, when combining TRO exposure alongside NDI in the same model, TROs were no longer significantly associated with overall cotinine levels.